The Effectiveness of Mobile Samsat Services in Improving Motor Vehicle Taxpayer Compliance in Bandar Lampung - Saputra, Aditya Budi; Wahyudi, Heru; Ananta, Prayudha; Darmawan, Arif (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This research examines how Mobile SAMSAT improves motor vehicle taxpayer compliance in Bandar Lampung City. Indonesia's growing fiscal demands for national expenditure and growth make regional taxes, especially motor vehicle tax, vital to local government revenue and public welfare. Motor vehicle tax contributes significantly to regional revenue, however taxpayer unfamiliarity with payment options and perceived burdensome SAMSAT office processes reduce compliance. In 2012, Bandar Lampung launched Mobile SAMSAT to provide door-to-door tax payment services, including annual Vehicle Registration Certificate (STNK) validation, Motor Vehicle Tax (PKB) payments, and Mandatory Road Traffic Accident Fund Contributions. This mixed-methods study used a Concurrent Triangulation Strategy to collect quantitative data from surveys and qualitative data from interviews and direct observation to evaluate program success factors. The results show that Mobile SAMSAT services promote taxpayer compliance via accessibility, clarity, and speed, boosting public trust and civic involvement in tax affairs. This efficacy is due to personnel response, appropriate service locations, and efficient administrative procedures.